Prevalence of Overweight and Obesity and its Associated Factors among Medical Students: A Case of Copperbelt University School of Medicine, Ndola, Zambia - Chilufya , Stella (Global Journal of Health Sciences, 2023)
Purpose: Overweight and obesity are defined as abnormal or excessive fat accumulation that presents a risk to health. They are a complex chronic global disease affecting people worldwide across all ages, sexes, ethnicities and nationalities. In 2016, more than 1.9 billion adults aged 18 years and older were overweight. Of these over 650 million adults were obese, 39% of adults aged 18 years and over (39% of men and 40% of women) were obese. Once considered a high - income country problem, overweight and obesity are now on the rise in low- and middle - income countries, particularly in urban settings. In Africa, obesity and overweight has been attributed to demographic and nutritional changes that have resulted from urbanization and the adoption of a western lifestyle which include lack of exercises and changes in dietary intake The objective of the study is to determine the prevalence of overweight and obesity and its associated factors among medical students from Michael Chilufya Sata Copperbelt University School of medicine, Ndola, Zambia. Methodology: A descriptive, quantitative cross - sectional study, which will use a standardized, structured self - administered questionnaire to survey the prevalence of overweight and obesity among medical students from Michael Chilufya Sata Copperbelt University School of medicine, Ndola, Zambia. 384 medical students will be allowed to participate in the study and data collected will be analyzed using the statistical package for social sciences (SPSS for windows). Findings: found a low prevalence of overweight and obesity among medical students at Ndola's copper-belt university. Male participants had a significantly higher prevalence than female participants, and most significant risk factor where associated with male student this might have been due to the disproportion in numbers between the male and female participants. Unique Contribution to Theory Practice and Policy: The study indicates a need for behaviour modification related to enhance lifestyle through increased physical activity and better nutritional practices among medical students.